Primary health care centers, extent of challenges and demand for oral health care in Riyadh, Saudi Arabia - Abeer Al-Jaber; Omar B. Da'ar (BMC, 2016)
Abstract Background As primary health care (PHC) centers in Saudi Arabia provide standardized preventive and curative oral health care (OHC) services, challenges remain. In addition, evidence of determinants of OHC seeking behavior is unknown. The aim of this study was to identify common challenges faced by patients seeking OHC in PHC centers and assess determinants of demand for OHC in Riyadh. Methods After institutional approval and piloting, 320 adult patients were sampled at two large PHC centers in October 2015. Using a modified version of General Practice Assessment (GAPQ) and New York State Department of Health (NYSDOH) Questionnaires, information about cumulative number of visits to a dentist, patient profiles, provider characteristics, and challenges were collected. We used descriptive statistics to summarize data and employed ordinal regression for analyzing extent of effects of challenges and determinants of demand for OHC. Results Oral health condition was reported to be good in 31 % of the patients, very good in 25 % of the patients, and fair in 20 % of the patients. More than half (53 %) of patients visited a dentist in the past 12 months once, 20 % twice, and 25 % at least three times. High cost of private clinic and unavailability of dentists were reported as the most common difficulties in seeing a dentist. Patients who were very satisfied with dental care and treatment plan, those with less than excellent oral health conditions and male patients had less number of cumulative visits to a dentist compared with patients with less satisfaction, patients with perceived excellent oral health, and female patients respectively. Conclusions Our findings provide a strong evidence of challenges faced by patients and determinants of demand for OHC seeking behavior. The findings can inform policy maker not only in patient satisfaction of OHC, but also implications on facilities and health care systems. We conclude with recommendations for future research, especially on oral health preventive measures in PHC centers that correct inherent dental problems and other underlying challenges.